Carbon‐Carbon Coupling on Inert Surfaces by Deposition of En Route Generated Aryl Radicals. Issue 50 (29th October 2020) - Galeotti, Gianluca; Fritton, Massimo; Lackinger, Markus
Abstract: To facilitate C−C coupling in on‐surface synthesis on inert surfaces, we devised a radical deposition source (RDS) for the direct deposition of aryl radicals onto arbitrary substrates. Its core piece is a heated reactive drift tube through which halogenated precursors are deposited and en route converted into radicals. For the proof of concept we study 4, 4′′‐diiodo‐ p ‐terphenyl (DITP) precursors on iodine‐passivated metal surfaces. Deposition with the RDS at room temperature results in highly regular structures comprised of mostly monomeric (terphenyl) or dimeric (sexiphenyl) biradicals. Mild heating activates progressive C−C coupling into more extended molecular wires. These structures are distinctly different from the self‐assemblies observed upon conventional deposition of intact DITP. Direct deposition of radicals renders substrate reactivity unnecessary, thereby paving the road for synthesis on application‐relevant inert surfaces. Abstract : Terphenyl biradicals are generated from iodinated precursors en route by deposition through the reactive drift tube of a newly devised radical deposition source. Upon deposition onto iodine‐passivated metal surfaces, the terphenyl radicals self‐assemble into ordered structures but remain active for C−C coupling into dimers and extended oligomers.